Transcription Regulator Yin-Yang 1: From Silence to Cancer - Zhu, Weidong (2011)
Yin Yang (YY) 1 represents the epitome of what is considered to be a “Swiss army knife” transcription factor and regulator. YY1 is a ubiquitous and multifunctional zinc-finger transcription factor member of the Polycomb group protein family, a group of homeobox gene receptors that can act as activators or repressors of transcriptional activity. Furthermore, YY1 can act as a redox sensor, adaptor molecule, and chromatin structure and function regulator. YY1’s characteristic function as transcriptional activator and repressor relies on its C2H2 (x4) zinc-finger structural DNA-binding motifs tangled with 2 specific regulatory domains. This structural conformation will render the activity of YY1 susceptible to changes in cellular redox status. YY1 also has been shown to undergo chromatin remodeling via interactions with histone acetyl transferase and histone deacetylase complexes. Both groups modify histones, resulting in altered chromatin structure. Herein, we will discuss the multiple roles and mechanisms of YY1 in the regulation of gene expression, its genetic factor functions, epigenetic regulatory activity, and its role as a redox sensor in the context of malignant neoplastic diseases.